Eesti kunstnikud = Artists of Estonia 1. - Bernstein, Boris; Helme, Sirje; Juske, Ants; Kelomees, Raivo; Komissarov, Eha; Liivak, Anu; Saar, Johannes; Treier, Heie; Vabar, Vappu; Varblane, Reet (Tallinn : Soros Center for Contemporary Arts Tallinn, 1998)
Annus, Siim-Tanel ; Arrak, Jüri ; Janov, Valve ; Kasemaa, Andrus ; Kask, Jüri ; Keskküla, Ando ; Kurismaa, Kaarel ; Kurvitz, Raoul ; Lapin, Leonhard ; Laurits, Peeter Maria ; Linnap, Peeter ; Malin, Ilmar ; Maran, Olav ; Meel, Raul ; Mudist, Peeter ; Ojaver, Jüri ; Okas, Jüri ; Põllu, Kaljo ; Runge, Sirje ; Sarapuu, Lembit ; Tammelaan, Tea ; Tolts, Andres ; Toomik, Jaan ; Vint, Aili ; Vint, Tonis
biog., bibliog. p. 249-309
Engels
Ests
boek
Keywords: Estland